Manifestation of Diabetes Mellitus in the mucous membrane of the Oral Cavity - Ibragimova F.I; Yodgorova. Sh.R (Research Parks Publishers, 2021)
Analysis of data obtained by examination of 40 patients with type I and types II diabetes was held. Examination included polls and dental examination. Polls were held with simple questions about diabetes duration, food tastes, hygienic care of oral cavity. To obtain information, we conducted a patient survey and a dental examination in parallel. Information from all patients' outpatient records was also taken into account